A montagem nos documentários sergipanos : uma análise dos premiados da Mostra Competitiva de Curtas Sergipanos (2005-2015) - Silva, Luzileide (2017)
This research seeks to observe how film editing used the various imagery and sound elements to constitute the narratives in documentaries made in Sergipe, assuming that the cinematographic editing, more than a simple technique, is a principle of creation through which the elements are structured by a certain order forging dramatic, comedic, abstract, reflective stories etc (SPENCE; NAVARRO, 2011). We try to verify how the selection and ordering of takes, shots, lines and sounds that compose the storytelling are choices, and they keep a certain connection with the representation of the real. In this study, we seek to understand how contemporary documentaries made in Sergipe are structured. The corpus is composed of the winners of the Competitive Screening of Short Film in Sergipe, held by Festival Ibero Americano de Cinema – Curta-Se, between 2005 and 2015. For this matter, we will observe the operational processes, which according to Fernando Morales Morante (2013) consist of technical operations that select and order the elements of image and sound, as well conceptual operations through procedures that elaborate the production of rhetoric, sensations and feelings.